The peculiar features of the mother archetypeʼs representation in Ukrainian proverbs and saying (Literatures of the World: Poetics, Mentality and Spirituality, 2018)
The article under consideration deals with the analysis of Ukrainian proverbs and sayings on the ground of presentation within the archetype of the mother, which is dominant in the thematic group about the peculiar features of the Ukrainian family. It is the mother's archetype that plays a key role for awareness of the features of the world picture of Ukrainians. The implication of positive features is connected with it. It is specially noted that the publication is represented various connotations of the image of the mother, which is created in Ukrainian proverbs and sayings. Mother is the core of the Ukrainian family in most of them, its image is associated with warmth, kindness, and prayer wisdom. Small forms analysis folk art proves the uniqueness of the mother for every person, as well as the need for a respectful attitude to her.
Keywords: proverb; sayings; archetype; mother